2020
DOI: 10.1038/s41598-020-78251-z
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prosocial behavior and decreasing selfishness in the lab and everyday life

Abstract: The tension between selfishness and prosocial behavior is crucial to understanding many social interactions and conflicts. Currently little is known how to promote prosocial behaviors, especially in naturally occurring relationships outside the laboratory. We examined whether a psychological micro-intervention would promote prosocial behaviors in couples. Across two studies, we randomized dyads of couples to a micro-intervention (15 min), which increased prosocial behaviors by 28% and decreased selfish behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…If a prosocial-oriented ACT intervention is proposed to fight the COVID-19 pandemic, alternative modes of delivery to face-to-face sessions, such as smartphone applications, video-conferencing or even self-help ACT, are recommended [ 21 , 59 ]. Apart from adopting ACT interventions, a recent study has found that even a very brief psychological flexibility training, for example using one experiential metaphorical exercise that targets at practising present-moment awareness, acceptance and values clarification, has been found to increase prosocial behaviour [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…If a prosocial-oriented ACT intervention is proposed to fight the COVID-19 pandemic, alternative modes of delivery to face-to-face sessions, such as smartphone applications, video-conferencing or even self-help ACT, are recommended [ 21 , 59 ]. Apart from adopting ACT interventions, a recent study has found that even a very brief psychological flexibility training, for example using one experiential metaphorical exercise that targets at practising present-moment awareness, acceptance and values clarification, has been found to increase prosocial behaviour [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mediating role of prosociality as hypothesized in this study was only partially supported, as such relationship was only found in the Hong Kong and the Eastern Europe samples. In literature, studies have indicated that engaging in various forms of prosocial behaviors (i.e., helping for the benefits of others) would promote emotional well-being, empathy and social connectedness [ 59 , 60 , 61 ], while such positive impacts could be brought by mechanisms through influencing oxytocin release and reward circuitry system in the brain [ 61 , 62 , 63 ]. Furthermore, transcending self-interest to advance the welfare of others becomes an intrinsic motivation for adhering to public health measures against the COVID-19 spread (e.g., physical distancing measures, wearing a face mask, social isolation rules to protect others from COVID-19, more than that of protecting oneself) [ 64 ], or to get vaccinated against COVID-19 [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is recommended for further ACT studies to investigate if addressing this malleable factor may nurture people with helping attitude and behaviour as an alternative way of coping. Also, recent research has indicated that even a very brief PF training, through using one experiential metaphorical exercise that aims to practice being in the present-moment awareness, may increase prosocial behavior [ 42 ].…”
Section: Discussionmentioning
confidence: 99%